Using z/VM for test and development environments : a roundup - Egeler, Klaus (IBM redbooks., 2007)
This IBM Redbooks publication shows the strengths of z/VM and how you can use these strengths to create a highly flexible test and production environment. Some of the strengths of z/VM that are shown in this book are that you can run Linux on z/VM, you can run a sysplex under z/VM, and you can develop code under z/VM for z/TPF. You can also provision Linux guests under z/VM. A vswitch allows you to connect all of your guests (all operating systems that run under z/VM) easily to the network. You can simulate your production environment on a sysplex. The intention of this book is to show the strengths of z/VM and how you can use these strengths to simulate your production Please note that the additional material referenced in the text is not available from IBM.